Quality of Life: A Case Report of Bullying in the Workplace. (2004) - Shahtahmasebi, Said
Abstract : The literature on bullying in the workplace describes the mental and physical ill health suffered by the victims and their families as the consequences of the bullying. The literature also discusses methods of bullying such as overt and covert physical and psychological abuse. The implications are that the consequences of abuse go far beyond the intended target; from impact on the working environment to individuals health to economic and financial loss. The literature suggests various recommendations to employers and managers to combat bullying at work. However, the common assumption within the literature has been that the bullying is done by a colleague, a line manager, or middle manager. Furthermore, it is often assumed that the executive/vice-chancellor, human resources, the trustees, or the governing board are unaware of bullying in their workplace. In this article, it is argued that cases of bullying (whether due to isolated individuals, competition, rivalry, power, or pure meanness as is reported in the literature) can only thrive in a bullying management culture. Therefore, debate and policy formulation must be directed at government level in the first instance. The case report is intended to raise some relevant issues to stimulate a debate and more research in this area.